2019
DOI: 10.1155/2019/3817879
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Study on Nude Mice Models of Gastric Cancer Treated with Modified Si Jun Zi Tang via HILIC UHPLC-Q-TOF/MS Analysis

Abstract: Recently, metabolomic methods have been used to explore the complex pathogenesis of cancer and the mechanism of action of traditional Chinese medicine (TCM) formulae. In this study, first, modified Si Jun Zi Tang (MSJZT) was prepared with strict quality control using the instrument method of ultra performance liquid chromatography and photodiode array detector (UPLC-PDA). Subsequently, in vivo experiments with tumour-bearing nude mice demonstrated that MSJZT exerted good antitumour effects. MSJZT not only sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…HILIC and UHPLC-Q-TOF/MS-based metabolomics approaches revealed that modified MSJZT decreased the mRNA and protein levels of LDH, glutamine synthetase, and PCYT2 in mouse plasma. These results suggested that the mechanisms underlying the anti-GC effects of MSJZT were at least partially mediated by regulating GC-induced energy metabolism dysfunction, such as amino acid, glycolysis, and lipid metabolism (Nie et al, 2019).…”
Section: Metabolomicsmentioning
confidence: 87%
“…HILIC and UHPLC-Q-TOF/MS-based metabolomics approaches revealed that modified MSJZT decreased the mRNA and protein levels of LDH, glutamine synthetase, and PCYT2 in mouse plasma. These results suggested that the mechanisms underlying the anti-GC effects of MSJZT were at least partially mediated by regulating GC-induced energy metabolism dysfunction, such as amino acid, glycolysis, and lipid metabolism (Nie et al, 2019).…”
Section: Metabolomicsmentioning
confidence: 87%
“… 28 A defect in lipid metabolism, for instance, may affect the proliferation and differentiation of tumour cells and may accelerate the occurrence and development of a range of cancer types. 29 In fact, a decrease in choline and cholesterol levels in the serum and tissues of patients with STAD can be employed as a biomarker for the early diagnosis of STAD. 30–32 These findings highlight the importance of defects in lipid metabolism and in cell membrane biosynthesis with respect to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites with both VIP > 1 and P < 0.05 were selected as the metabolites with significant differences. Accurate mass number matching (tolerance < 25 ppm) was used for identification of the metabolites and secondary spectrum matching and the laboratory self-built database was searched (Nie et al, 2019;. Finally, we analyzed the correlation of significant differences in metabolites in order to further understand the relationships between metabolites in the process of biological state changes.…”
Section: Discussionmentioning
confidence: 99%